Targeting nominal GDP or prices: Guidance and expectation dynamics - Kaushik Mitra; Seppo Honkapohja (Bank of Finland, 2014)
We examine global dynamics under infinite-horizon learning in New Keynesian models where monetary policy practices either price level or nominal GDP targeting and compare these regimes to inflation targeting. These interest-rate rules are subject to the zero lower bound. Robustness of the three rules in learning adjustment are compared using criteria for the domain of attraction of the targeted steady state, volatility of inflation and output and sensitivity to the speed of learning parameter. Performance of price-level and nominal GDP targeting significantly improves if the additional guidance in these regimes is incorporated in private agents' learning.
URN:NBN:fi:bof-20140807627
Keywords: E63; E52; E58; 330; Adaptive Learning; Monetary Policy; Inflation Targeting; Zero Interest Rate Lower Bound